Analisis manajemen risiko pembiayaan pada akad mudharabah perbankan syariah - Sonia, Lailatul Izzah (Maliki Interdisciplinary Journal, 2024)
This research aims to understand the risks that often occur in financing with mudharabah contracts. The method used in this research is by using a literature review of previous research. The results of this research are that the risks associated with mudharabah contracts include market, liquidity, operational, legal, reputation, strategic, compliance and performance risks. There are also other risks such as credit risk and investment risk. Literature studies show that these risks can occur when customers use funds not in accordance with the contract or through intentional mistakes. One of the risks identified is shrinking risk, which is related to a decrease in the financial value of mudharabah due to certain business factors.